A cognitive analysis of war metaphors in English business texts and their Arabic translations. Issue 1 (2nd January 2022) - Shehab, Ekrema; Nazzal, Rema
ABSTRACT: The main role of metaphor in economic discourse is essential in facilitating our understanding of some business situations or concepts. This article offers a comprehensive analysis of English business war metaphors in their immediate context of use and their Arabic equivalents as they naturally occur in authentic business texts. The data of the study are drawn from business articles on BBC, CNN, Financial Times and Project Syndicate websites. The study departs from the traditional view of metaphor as a linguistic expression that has only an aesthetic value in the text and it examines how metaphors shape our perception of the business world as they express business ideas. The study reveals that Arabic and English business metaphorical expressions share both similar and different cognition modes and hence four strategies of translating English war metaphors into Arabic are discussed: SL war metaphor is rendered into its comparable metaphor in Arabic using literal translation; SL war source domain is shifted into another TL source domain; an English metaphor is toned down into an Arabic non-metaphor and finally an English non-metaphor is shifted into an Arabic metaphor.